Imaging of Fibrosis in Chronic Pancreatitis - Yamashita, Yasunobu; Ashida, Reiko; Kitano, Masayuki (Frontiers in Physiology, 2022)
Chronic pancreatitis (CP) describes long-standing inflammation of the pancreas, which leads to irreversible and progressive inflammation of the pancreas with fibrosis. CP also leads to abdominal pain, malnutrition, and permanent impairment of exocrine/endocrine functions. However, it is difficult to assess CP pathologically, and imaging modalities therefore play an important role in the diagnosis and assessment of CP. There are four modalities typically used to assess CP. Pancreatic duct features are assessed with magnetic resonance cholangiopancreatography (MRCP) and endoscopic retrograde cholangiopancreatography (ERCP). However, ERCP is a rather invasive diagnostic modality for CP, and can result in adverse events such as post-ERCP pancreatitis. Computed tomography (CT) is often the most appropriate initial imaging modality for patients with suspected CP, and has high diagnostic specificity. However, CT findings typically only appear in advanced stages of CP, and it is difficult to detect early CP. Endoscopic ultrasonography (EUS) provides superior spatial resolution compared with other imaging modalities such as CT and magnetic resonance imaging (MRI), and is considered the most reliable and efficient diagnostic modality for pancreatic diseases. The EUS-based Rosemont classification plays an important role in diagnosing CP in clinical practice. Evaluation of tissue stiffness can be another option to assess the diagnosis and progression of CP, and MRI and EUS can be used to assess CP not only with imaging, but also with elasticity measurement. MR and EUS elastography are expected to provide new alternative diagnostic tools for assessment of fibrosis in CP, which is difficult to evaluate pathologically.